STOMp: sexual function trial of overactive bladder medication. Issue 1 (12th January 2023) - Polland, Allison; Hamner, Jennifer Joy; Arunachalam, Divya; Dwarica, Denicia Shane; Gupta, Ankita; Pennycuff, Jon F; Tran, Ann D; Tefera, Eshetu; Meriwether, Kate V; Gutman, Robert E
Abstract: Background: Female sexual function has been shown to improve with overactive bladder (OAB) treatment. Aim: The objective of this study was to evaluate the effects of anticholinergics (ACHs) or a beta-agonist (BAG) on female sexual function. Methods: This was a prospective multicenter cohort study. Sexually active women with OAB completed the Overactive Bladder questionnaire (OAB-q) and Female Sexual Function Index (FSFI) prior to and after 12 weeks of therapy. Sample sizes of 63 per group were calculated to detect a clinically relevant difference in the FSFI. Outcomes: The primary outcome was FSFI change from baseline at 12 weeks. Results: A total of 157 patients were recruited, and 91 completed follow-up (58/108, ACH; 31/49, BAG). There were within-group FSFI differences from pre- to posttreatment: a worsening of arousal in the ACH group ( P = .046) and an improvement in overall FSFI ( P = .04) and pain ( P = .04) in the BAG group. After treatment, postmenopausal women in the BAG group had significantly better overall FSFI ( P = .01), desire ( P = .003), arousal ( P = .009), and orgasm ( P = .01). Clinical Implications: While further research is necessary, this study provides information about the comparative effects of OAB treatments on female sexual function, which may ultimately lead to better patient selection and outcomes. Strengths and Limitations: While there was no difference between the subjects who completed the study and those who did not, the study remained underpowered after the loss to follow-up. The multicenter cohort design allows for generalizability of results. Conclusion: Although this study was underpowered, an improvement in overall sexual function was seen with BAGs, while ACHs were associated with worsening aspects of sexual function.